The role of the lysine histone methylase KMT2D in chronic myeloid leukemia - Schlemminger, Lina; Nagel, Inga; Vater, Inga; Cascorbi, Ingolf; Kaehler, Meike (Frontiers in Pharmacology, 2025)
Chronic myeloid leukemia (CML) can be effectively treated inhibiting the disease-causing BCR::ABL1 kinase by tyrosine kinase inhibitors (TKIs). Although therapy is initially tremendously successful, resistance may occur in up to 25% of CML patients. Besides aberrations in the BCR::ABL1 kinase domain, a variety of resistance mechanisms are currently discussed, among them epigenetic reprogramming. The histone-modifying enzyme lysine methyltransferase 2D (KMT2D/MLL2) belongs to the most frequently mutated genes in cancer and is also known for its association with hereditary Kabuki syndrome. However, its role in CML is widely unknown. In the present study, we analyzed the role of the KMT2D p. (Arg191Trp) variant in imatinib-resistant CML, which was recurrently acquired in imatinib resistance in vitro. SiRNA-mediated KMT2D knockdown, but also introduction of the p. (Arg191Trp) variant into treatment-naïve K-562 cells led to impaired imatinib susceptibility visible by increased cell numbers, proliferation rates and metabolic activities under imatinib exposure (p < 0.001). The effect of KMT2D p. (Arg191Trp) could be overcome by inhibiting histone demethylation with the demethylase inhibitor LSD1. In addition, rescue of KMT2D expression in imatinib-resistant cells reinstated the response to imatinib treatment. Furthermore, gene expression analysis revealed upregulation of CCNE2 in cells harboring KMT2D p. (Arg191Trp) potentially explaining increase in cell proliferation under imatinib exposure. Overall, our findings demonstrate that the loss of the tumor suppressor KMT2D promotes TKI resistance in CML. Thus, KMT2D status could serve as an additional biomarker for TKI resistance, while restoration of its expression might be a therapeutic option to overcome this resistance.